Studi Komparatif Motivasi Belajar Berdasarkan Gender Siswa Kelas V SDN 112 Pekanbaru - Sarita, Widya Rahma; Syahrilfuddin, Syahrilfuddin; Antosa, Zariul (TSAQOFAH, 2023)
This research aims to find out whether there is a difference in learning motivation between male and female students at SDN 112 Pekanbaru for the 2022/2023 academic year. The type used in this research is comparative quantitative where the researcher wants to compare the learning motivation of male and female students, the subjects of this research are the VA VB and VC classes, the sample in this study was 53 students consisting of 27 male students and 26 male students Woman. Data collection in this research was by distributing questionnaires containing statements about learning motivation. The results of the hypothesis test were carried out using the t test with a significance result of 0.201>0.005 which shows that there is no significant difference in learning motivation between male and female students.